2005
DOI: 10.1111/j.0307-6946.2005.00726.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of adult nutrition on the relationship between body size and reproductive parameters in a parasitoid wasp

Abstract: 1. An important constraint upon life-history evolution in parasitoids is the limit imposed by body size on allocation of limited metabolic resources to different fitness-related physiological functions such as reproduction and survival.2. The influence of adult nutrition on reproductive and maintenance variables was studied in the synovigenic ectoparasitoid Mastrus ridibundus, and it was determined whether resource allocation to these different functions depends on body size.3. Over the course of adult life th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 57 publications
4
45
0
Order By: Relevance
“…The observed egg load of L. fabarum was directly related to body size, as has been demonstrated in other parasitoid species (O'Neill & Skinner, 1990;Jervis et al, 2001;Bezemer et al, 2005). For example, Sagarra et al (2001) showed that body size was not only positively correlated with lifetime fecundity in female Anagyrus kamali Moursi, but also with longevity and daily oviposition rate.…”
Section: Discussionsupporting
confidence: 68%
“…The observed egg load of L. fabarum was directly related to body size, as has been demonstrated in other parasitoid species (O'Neill & Skinner, 1990;Jervis et al, 2001;Bezemer et al, 2005). For example, Sagarra et al (2001) showed that body size was not only positively correlated with lifetime fecundity in female Anagyrus kamali Moursi, but also with longevity and daily oviposition rate.…”
Section: Discussionsupporting
confidence: 68%
“…Thus, within a population of parasitoids the larger ones are likely to contribute more to the increase of the parasitoid population or suppression of the host population. It is likely that this increased host attack rate can be attributed to the greater energy reserves and more advanced egg production of the larger females (Ellers et al, 1998;Bezemer et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Latania scale manages to reach a survival rate about seven times higher than the A. diaspidis parasitoid and determines the time needed in the field between releases. In the ectoparasitic species Mastrus ridibundus (Gravenhorst) (Hymenoptera: Ichneumonidae), higher longevity was observed in females that were fed than those that received little food (Bezemer et al, 2005). It has also been determined in the Eupelmus vuilletti (Crawford) (Hymenoptera: Eupelmidae) species that host-feeding increases both longevity and egg production (Giron et al, 2004).…”
Section: Survivalmentioning
confidence: 99%
“…Parasitoid females use a great quantity of reserved lipids during the first 24 h of life, which could be a limiting factor mainly in the smaller females (Rivero and West, 2002). In some species, larger females produce a higher number of eggs and a higher egg maturation rate (Bezemer et al, 2005). In A. melinus fed with Aspidiotus nerii, it was determined that an increase in reproductive activity would also occur with an external food supply with sugars (Heimpel et al, 1997).…”
Section: Fecunditymentioning
confidence: 99%